Quanto è “verde” il PNRR? Le par Quanto è “verde” il PNRR? Le parole e i fatti - Olmi, Fabio (Chimica nella Scuola, 2024)
The article examines the “green” Mission 2 of the PNRR which concerns the energy aspects of the ecological transition with the aim of verifying the progress of its development. In particular, the essential elements of the Component 2 of this Mission are examined. It emerges that the promotion of renewable energy is heavily penalised, whereas research and development of hydrogen and development of charging station installations for electric cars are taken in consideration. The rapid progress in biomethane production, which however does not solve the problem of decarbonization, is also considered.